ANALYTICAL STUDY OF MHD COUPLE STRESS CASSON NANOFLUID-FLOW OVER STRETCHING SURFACE - Rehman, Ali; Jan, Rashid; Elamin, Abd Elmotaleb A. M. A.; Abdel-Khalek, Sayed; İnç, Mustafa (Vinca Inst Nuclear Sci, 2022)
The impact of coupled stress casson nanofluid-flow over a stretching surface will be examined in this paper. The fundamental controlling PDE are transformed using the stated similarity transformation into a pair of coupled, non-linear ODE, one for velocity and the other for temperature distribution. The modeled flow problem's approximate analytical solution was discovered using the approximate analytical approach. Graphs are used to illustrate the effects of different factors. A table illustrating the relationship between the Nusselt number and skin friction is provided.
Keywords: nanofluid-flow; computational analysis; MHD; couple stress; stretching surface